Digestive Disease Mortality Dynamics During New Coronavirus Infection Pandemic in Different Subjects of Russian Federation - V. T. Ivashkin; A. A. Sheptulin; O. P. Alekseeva; S. A. Alekseenko; A. Yu. Baranovsky; O. Yu. Zolnikova; N. V. Korochanskaya; S. N. Mammayev; I. B. Khlynov; V. V. Tsukanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. An analysis of digestive disease mortality dynamics in different subjects of the Russian Federation in course of the new coronavirus infection pandemic.Key points. In most subjects of the Russian Federation, the first half of 2021 enduring the COVID-19 pandemic has witnessed a higher overall mortality from digestive diseases and from peptic ulcer, liver and pancreatic illnesses compared to the same period in 2020. This situation may have roots in both the adverse impact of coronavirus infection on pre-existing digestive diseases and shortages in providing specialty medical aid to gastroenterological patients during the pandemic. Improved outpatient care and remote counselling, as well as successful educational measures, may reduce gastroenterological disease-associated mortality.Conclusion. Most regions of Russia have registered a growing mortality from digestive diseases at the new coronavirus infection pandemic due to the SARS-CoV-2 adverse impact on illness progression, as well as imposed difficulties in providing specialty medical aid.